A study of binding interactions between terpyridine derivatives and cucurbit[10]uril. Issue 8 (3rd August 2018) - Deng, Yuanyuan; Yin, Hang; Zhao, Zhiyong; Wang, Ruibing; Liu, Simin
Abstract: The binding interactions of a series of 2, 2′:6′, 2″-terpyridine (TPY) derivatives and their metal complexes with cucurbit[10]uril (CB[10]) were investigated by 1 H NMR, UV/Vis, emission spectroscopy, and ESI mass spectrometry. 1 H NMR titrations revealed CB[10] could encapsulate methylated TPY (MTPY), and the binding ratio between guest MTPY and host was 1:1 and 2:1 via ESI-MS characterization. For the transition metal complexes composed of Fe(II) or Ru(II) or Rh(III) and TPY derivatives, the octahedral TPY−metal−TPY core can be included in the cavity of CB[10]. Three binding modes (1:1, 1:2 and 1:3) have been detected for the binding of the metal−MPTY complexes with CB[10] by ESI-MS. Abstract :